The struggle of localisation: Can the Grand Bargain 2.0 redeem the failure of its precursor? - Karen Wulff Sørensen (Roskilde University, Department of Social Sciences and Business, Socio-Economic Research Centre (SECO), 2022)
This working paper discusses the topic of localisation, which is an integral part of the Grand Bargain agenda. To understand what barriers have prevented the success of localisation, this paper explores how international Danish-based NGOs relate to the policy intentions defined in the localisation workstream emanating from the 2016 Grand Bargain. The paper argues that the lack of consensus regarding the meaning of localisation - as a concept, policy and in practice - fosters a gap between policy intentions and practice, which enables the interests of international organisations to be privileged. Through a thematic analysis of interviews with five international Danish-based NGOs, the paper argues that three prevailing problem areas prevent localisation from creating transformational change on the ground in the humanitarian and development sector: 1) The intertwinedness of the localisation discourse with desirable organisational images and narratives of 'appropriate aid practices', which maintains localisation at a global political level with lack of practical implementation on local levels; 2) organisational structures can serve as a loophole to live up to localisation commitments without creating change within the organisation's approaches and practices; and 3) the decision-making power to determine the prospects of localisation lies with the resourceful and structurally privileged actors within the development and humanitarian field. A common issue identified in this threefold analysis is the accentuation of localisation as global policy discourse in which locally led practice is pushed to the background. Lastly, the paper asks whether the Grand Bargain 2.0, with its updated framework from 2021, can redeem the failure of its precursor.
Keywords: 330